Innovations in science teacher education in the Asia Pacific (Advances in research on teaching ;, 2014)
The chapters in this book will focus on pre-service and in-service science teacher education, because both are equally important. With case studies for China, Japan, Korea and Taiwan topics include: Professional Development of Chemistry Teachers in the New Curriculum, Using Classroom Observation to Assist Teacher Professional Development and Science Teacher Education and Science as Inquiry: Promises and Dilemmas.